Improving the Quality of Learning Through Project Based Learning (PjBL) With the STEAM Approach in CAD Courses in the Department of Automotive Engineering Universitas Negeri Padang - Irma Yulia Basri; M. Giatman; Mukhlidi Muskhir; Hansi Effendi; Ambiyar Ambiyar; Eni Elfina; Tri Putra Yuliardi (invotek, 2023)
The application of the Project Based Learning (PjBL) learning model in CAD courses has so far not been satisfactory. the results of the design drawings produced by students could not be implemented because the size, component layout, beauty did not meet the criteria. As a result, the students failure rate in CAD courses from 2019 to 2022 is quite high. PjBL with the STEAM approach is a solution because with STEAM the design of the images produced by students is based on criteria Science, Technology, Engineering, Art and Mathematics. This type of research uses Classroom Action Research, which is an examination of activities that are deliberately raised and occur in a class, and have 3 Cycle. The process of implementing the research consists of four components, namely planning, action, observation, and reflection. The population is Diploma 3 Automotive Engineering Students in Faculty of Engineering, Universitas Negeri Padang (FT UNP) who are enrolled in the CAD course for the Semester January - June 2022 and totaling 46 students. The data collection techniques through observation sheets and students performance in designing drawings using CAD software. The results of the study show that the implementation of PjBL with the STEAM approach can improve the quality of learning. The quality of learning observed is the activity of lecturers and students and learning outcomes. The percentage of lecturer activity in the learning process is 77% and increases in cycles 2 and 3 with percentages of 85.90% and 89.6%. While students activity in the learning process cycle 1 obtained a percentage of 62.4%, increased in cycles 2 and 3 of 73.20% and 87.70%. courses computer aided design using a project-based learning approach STEAM can increase the average value of students. This is based on the average grade of students drawing projects in cycle 1 of 33.04, Whereas in cycle 2 it was 69.80 and the average students score in cycle 3 was 76.42.